Social media campaigns and domestic products consumption: a study on an emerging economy - Sneha Rajput; Ganesh Dash; Nischay Upamannyu; Bhuvanesh Kumar Sharma; Prakash Singh (Cogent Business & Management, 2022)
The growth of the "Internet" and the subsequent use of smartphones has led to heavy social media usage in recent years. Social media campaigns have been successful in influencing purchase intention. Ethnocentrism also affects the purchase intention (PI) of domestic products. ETH is an evolving field, particularly for the purchase intention of domestic products. Considering the same, we examined the impact of social media campaigns (SMC) and ethnocentrism (ETH) on the purchase intention of domestic products. The mediating role of ethnocentrism and the moderating role of country-of-origin image (COOI) are examined further. The proposed hypotheses were examined using structural equation modeling. Data was collected from 431 avid social media users in a region that saw massive protests through social media campaigns. The results exhibit the positive impact of social media campaigns and ethnocentrism positively over the purchase intention of domestic products. In addition, ethnocentrism was found to be a mediator between social media campaigns and the purchase intention of domestic products. Moreover, the country of origin image strengthens the positive relationship between social media campaigns and the purchase intention of domestic products. However, COOI dampened the positive relationship between social media campaigns and ethnocentrism. This study provides fresh insights and implications for theory and practice.
Keywords: 650; country-of-origin image; domestic products; emerging economy; ethnocentrism; purchase intention; Social media campaigns